2017
DOI: 10.1021/acs.jafc.7b00357
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Ecklonia cava Polyphenol Extract on Renal Inflammation Associated with Aberrant Energy Metabolism and Oxidative Stress in High Fat Diet-Induced Obese Mice

Abstract: Immoderate fat accumulation causes both oxidative stress and inflammation, which can induce kidney damage in obesity. Previously, Ecklonia cava has shown anti-inflammatory and antioxidative effects. Our group aimed to investigate whether E. cava polyphenol extract (ECPE) improves renal damage in high fat diet (HFD)-induced obese mice through regulation of not only energy metabolism but also oxidative stress and inflammation. After obesity induction by HFD, the mice were treated with different dosages of ECPE (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 51 publications
2
37
0
Order By: Relevance
“…Immoderate fat accumulation causes both oxidative stress and inflammation, which can induce kidney damage in obese subjects. Eo et al ( 2017 ) studied the renal protective effects on high-fat diet obese mice of different dosages of ecklonia cava polyphenol extract given by gavage for 12 weeks, finding that its administration lowered inflammation and oxidative stress. In addition, supplementation with this polyphenol extract significantly up-regulated renal SIRT1, PGC-1α, and AMPK, which are associated with renal energy metabolism, thereby improving the aberrant renal energy metabolism induced by a high-fat diet.…”
Section: Obesity and Diabetesmentioning
confidence: 99%
“…Immoderate fat accumulation causes both oxidative stress and inflammation, which can induce kidney damage in obese subjects. Eo et al ( 2017 ) studied the renal protective effects on high-fat diet obese mice of different dosages of ecklonia cava polyphenol extract given by gavage for 12 weeks, finding that its administration lowered inflammation and oxidative stress. In addition, supplementation with this polyphenol extract significantly up-regulated renal SIRT1, PGC-1α, and AMPK, which are associated with renal energy metabolism, thereby improving the aberrant renal energy metabolism induced by a high-fat diet.…”
Section: Obesity and Diabetesmentioning
confidence: 99%
“…Eo, Park, Jeon, & Lim, found that Ecklonia cava polyphenol extract treatment upregulated renal SIRT1, AMPK, Nrf2, and NQO1 in a model of obesity. FXR preserves normal hepatic metabolism of bile acids, glucose, and lipids, stimulates hepatic regeneration and repair after injury, shields liver cells from death, and stimulates cell survival, preventing inflammatory damage, and tumor genesis.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK and SIRT1 levels in TAA-induced hepatic cirrhosis Di et al (2017). stated that cichoric acid (CA) amplified pAMPK level, activated the nuclear receptor factor-2 (Nrf2), a master regulator of antioxidant enzymes with increasing antioxidant enzymes expression as NQOR1 Eo, Park, Jeon, & Lim, 2017. found that Ecklonia cava polyphenol extract treatment upregulated renal SIRT1, AMPK, Nrf2, and NQO1 in a model of obesity.…”
mentioning
confidence: 99%
“…[94] However, excessively elevated ROS level would destroy redox balance and give rise to cellular oxidative stress, thus evoking serious damage to biomacromolecules and tissue inflammation. [94] Solid evidences have demonstrated that cellular oxidative stress can cause a variety of diseases, including chronic inflammation, [95] neural dysfunction, [96] atherosclerosis, [97] diabetes, [98] cancer, [99] and cardiovascular diseases. [100] Robust and high-efficient ROS scavengers play critical roles in protecting cells from oxidative stress as they can counteract the detrimental effects induced by excessive ROS and sustain redox balance of the formation and reduction of ROS.…”
Section: Oxidative-stress Cytoprotectionmentioning
confidence: 99%